2017
DOI: 10.1371/journal.pone.0176958
|View full text |Cite
|
Sign up to set email alerts
|

Development of prostate specific membrane antigen targeted ultrasound microbubbles using bioorthogonal chemistry

Abstract: Prostate specific membrane antigen (PSMA) targeted microbubbles (MBs) were developed using bioorthogonal chemistry. Streptavidin-labeled MBs were treated with a biotinylated tetrazine (MBTz) and targeted to PSMA expressing cells using trans-cyclooctene (TCO)-functionalized anti-PSMA antibodies (TCO-anti-PSMA). The extent of MB binding to PSMA positive cells for two different targeting strategies was determined using an in vitro flow chamber. The initial approach involved pretargeting, where TCO-anti-PSMA was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…In this study, the STEAP‐1–targeted SonoVue microbubble enhanced the ultrasound signal intensity remarkably compared with ordinary SonoVue microbubble. Our results are in agreement with the previous report of the PSMA target microbubble by Zlitni et al and Wang et al Therefore, STEAP‐1–targeted SonoVue microbubbles could bind with their targets expressed by tumors in the nude mouse xenograft models and enhanced the intensities of ultrasound imaging signals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the STEAP‐1–targeted SonoVue microbubble enhanced the ultrasound signal intensity remarkably compared with ordinary SonoVue microbubble. Our results are in agreement with the previous report of the PSMA target microbubble by Zlitni et al and Wang et al Therefore, STEAP‐1–targeted SonoVue microbubbles could bind with their targets expressed by tumors in the nude mouse xenograft models and enhanced the intensities of ultrasound imaging signals.…”
Section: Discussionsupporting
confidence: 93%
“…The 5‐year survival rate of PCa is around 99% in cases of early detection. When PCa has spread beyond the prostate, survival reduces significantly . Transrectal ultrasound‐guided biopsy is the gold standard for PCa diagnosis, which is generally performed in patients with elevated serum levels of prostate‐specific antigen.…”
mentioning
confidence: 99%
“…Prostate‐specific membrane antigen is highly expressed in prostatic intraepithelial neoplasia, hormone‐dependent PCa, non–hormone‐dependent PCa, and metastases . The PSMA antibody was developed to specifically bind to PCa cells in vivo, and some studies have shown that the application of PSMA‐targeting or other specific antigen‐targeting MBs can improve the diagnostic accuracy of US …”
Section: Discussionmentioning
confidence: 99%
“…13,14 The PSMA antibody was developed to specifically bind to PCa cells in vivo, 16,18 and some studies have shown that the application of PSMAtargeting or other specific antigen-targeting MBs can improve the diagnostic accuracy of US. [29][30][31] Although the vascular endothelial gap is expanded in some disease states, such as in tumors, only particles of less than 700 nm in diameter are allowed to pass through. 32 Targeted MBs have a wide range of clinical applications, but because they are larger than 1000 μm, it is difficult for MBs to enter tumor tissue through the vessel wall and specifically bind to tumor cells; in addition, the short in vivo halflife of MBs results in an insufficient time frame for imaging the target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation